Effects of nutritional status on short-term prognosis after minimally invasive pancreaticoduodenectomy - Zheyu Xu; Jingtao Chen; Yiping Mou; Ou Li; Yucheng Zhou (Scientific Reports)
Abstract Minimally invasive pancreaticoduodenectomy (MIPD) has been routinely performed in major centers, and its feasibility and efficacy in tumor treatment have been highly recognized. Malnutrition has been associated with higher rates of morbidity, and increased mortality in surgical patients. The effect of the nutritional status on MIPD outcomes still remains unclear and controversial. The clinical data of 207 consecutive patients who had MIPD between June 2017 and December 2022 were retrospectively analyzed. A multidimensional nutrition assessment was performed before surgery. Multivariable analysis and propensity score matching (PSM) was performed to identify the association of preoperative nutritional status on postoperative short-term prognosis(Morbidity–Mortality, Clavien-Dindo classification ≥ IIIa, postoperative pancreatic fistulas and biliary fistula). In the multivariable analysis, sarcopenia (OR 9.74, 95% CI 3.34–43.03) was associated with postoperative morbidity and sarcopenia (OR 6.74, 95% CI 2.24–30.24) was associated with major complications. In the cohort after PSM, sarcopenia remained independently associated with morbidity (OR 12.44, 95% CI 3.72- 59.16) and major complications (OR 8.14, 95% CI 2.13- 43.83). Sarcopenia before MIPD has an impact on postoperative outcomes. Nutritional status assessment, especially sarcopenia, should be part of the routine preoperative procedures to provide early and appropriate nutritional support for MIPD patients.